2009
DOI: 10.1073/pnas.0903922106
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous properties of the acoustic excitations in glasses on the mesoscopic length scale

Abstract: The low-temperature thermal properties of dielectric crystals are governed by acoustic excitations with large wavelengths that are well described by plane waves. This is the Debye model, which rests on the assumption that the medium is an elastic continuum, holds true for acoustic wavelengths large on the microscopic scale fixed by the interatomic spacing, and gradually breaks down on approaching it. Glasses are characterized as well by universal low-temperature thermal properties that are, however, anomalous … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
166
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(195 citation statements)
references
References 42 publications
(94 reference statements)
26
166
0
Order By: Relevance
“…This leads to a plateau in the diffusivity consistent with the results of Fig.(1.8). This analysis predicts a drop in the speed of sound near ω * , a subtle effect recently observed numerically at the Boson peak frequency in model glasses [42]. In the case where the isostatic state is a square lattice [32], the Ioffe-Regel criterion is satisfied at the crossover frequency ω * and ℓ s is of order the lattice spacing.…”
Section: Diffusivity Quasilocalized Modes and Anharmonicity Diffusivitysupporting
confidence: 51%
“…This leads to a plateau in the diffusivity consistent with the results of Fig.(1.8). This analysis predicts a drop in the speed of sound near ω * , a subtle effect recently observed numerically at the Boson peak frequency in model glasses [42]. In the case where the isostatic state is a square lattice [32], the Ioffe-Regel criterion is satisfied at the crossover frequency ω * and ℓ s is of order the lattice spacing.…”
Section: Diffusivity Quasilocalized Modes and Anharmonicity Diffusivitysupporting
confidence: 51%
“…The scale ξ of the elastic heterogeneities can be assessed by measuring the local elastic properties as a function of a coarse graining size, and monitoring the convergence towards macroscopic properties [3]. The elastic continuum approximation for the acoustic excitations breaks down on a mesoscopic wavelength comparable to ξ, where a marked reduction of the sound velocity and strong scattering were observed [10,11]. It has been suggested that the elastic heterogeneity is closely linked to several unusual properties of glasses, which include low-temperature thermal properties [12], an excess vibrational density of states, known as the "Boson peak" [13,14], and anomalous acoustic properties [10,11,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The elastic continuum approximation for the acoustic excitations breaks down on a mesoscopic wavelength comparable to ξ, where a marked reduction of the sound velocity and strong scattering were observed [10,11]. It has been suggested that the elastic heterogeneity is closely linked to several unusual properties of glasses, which include low-temperature thermal properties [12], an excess vibrational density of states, known as the "Boson peak" [13,14], and anomalous acoustic properties [10,11,[15][16][17]. Theoretical models [18,19] have been proposed to relate the boson peak and the associated thermal and acoustic anomalies to a randomly fluctuating shear modulus.…”
Section: Introductionmentioning
confidence: 99%
“…This frequency range is also at the lower edge of the region accessible to molecular dynamics simulations. 3 A variety of theoretical models has been proposed to explain these low-frequency (∼1 THz) vibrations. Among them we may recall the soft potential model, 4 the mode-coupling theory applied to the vibrations in glasses, 5 models on a lattice 6 or on the continuum 7 with randomly fluctuating elastic constants, and harmonic models where the atoms vibrate around topologically disordered configurations.…”
Section: Introductionmentioning
confidence: 99%
“…25 These experimental results have been confirmed by molecular dynamics simulations of a Lennard-Jones glass performed on an exceptionally large simulation box, containing 10 7 particles. 3 The observation of these elastic anomalies requires a very high accuracy which has been attained only in recent years, thanks to the continuous development of the IXS technique. The particular case of vitreous silica has been deeply studied by means of IXS in the past, [26][27][28][29][30][31][32][33][34][35] but these fine features of the dynamics were hidden by the noise in the first experiments.…”
Section: Introductionmentioning
confidence: 99%